Characterization of genomic profiling of Mexican women with breast cancer using EndoPredict - Diana Carolina Correa Sandoval; Jose Luis Guzman Murguia; Diego Alberto Guajardo Nieto (Cancer Treatment and Research Communications)
Purpose: In the context of rising breast cancer incidence and mortality rates in Mexico, our study delves into the genomic landscape of Mexican women diagnosed with stage I-III breast cancer. Methods: Employing the EndoPredict test for genomic analysis, our retrospective, cross-sectional study explores correlations between genomic expression and immunohistochemistry (IHC). Results: Among 50 female patients, risk stratification by IHC revealed 50 % as high risk and 50 % as low risk, with notable clinical and histological distinctions between the two groups. High-risk samples exhibited larger tumors, higher histological grades, and more positive lymph nodes. Immunohistochemistry results displayed a moderate concordance (kappa Cohen´s 0.48) with the EndoPredict test, emphasizing its clinical reliability over IHC. Conclusions: The study advocates for the integration of genomic tools, particularly the EndoPredict test, in the management of breast cancer in Mexican women for enhanced precision in treatment decisions. Our findings contribute valuable insights to the evolving landscape of breast cancer diagnosis and management in the Mexican population.